Be wary about occult metastasis to cervical level I lymph node from a case of thyroglossal duct cyst carcinoma. Issue 3 (25th May 2022) - Chow, Tam Lin; Lee, Clary K. L.
Abstract: Background: Thyroid carcinoma arising from thyroglossal duct cyst is rare. Papillary thyroid carcinoma is the most frequent subtype but its biological behaviour, such as pattern of nodal spread, is largely elusive. Method: We report one case of locally advanced papillary carcinoma arising from thyroglossal duct cyst with subclinical cervical level I lymph node metastasis which is an unexpected drainage area for its counterpart from the thyroid. Results: Sistrunk operation, total thyroidectomy and bilateral cervical level I lymph node dissection were performed. I 131 ablation was administered postoperatively. Patient remained disease free after a follow‐up of 7 years. Conclusion: The reported case shed light on the nodal spread from thyroglossal duct cyst cancer and has bearing on the plan of surgical management.